Evaluation of the Merdeka Curriculum P5 in the Perspective Islamic Education Management - Zulfida Aulia Fatimah (Jurnal Ilmu Manajemen dan Pendidikan, 2025)
The ministry of education and culture has officially launched the Merdeka Curriculum as a response to global challenges. This new curriculum has been implemented by various schools in Indonesia. The implementation of this learning process has encountered various obstacles to date. Therefore, an evaluation is necessary. This research was conducted using a descriptive qualitative approach based on primary and secondary data. The data analysis used was inductive from the beginning of the research until conclusions were drawn. The results of the study show that the implementation of the Merdeka Curriculum for the Pancasila Student Profile Strengthening Project (P5) still faces various obstacles. These include differences in the level of understanding and readiness among teachers in various regions regarding the characteristics of the curriculum, a lack of teacher training and mentoring, and a lack of readiness in educational infrastructure, such as a lack of internet access or digital based learning tools. These problems can be minimized by maximizing the available facilities. However, the obstacles experienced to date have not been optimally resolved, especially in remote areas due to limited internet access. Therefore, continuous evaluation is needed as an improvement and planning for the next educational process.